DEVELOPMENT AND VALIDATION OF SPECTROPHOTOMETRIC METHODS FOR ESTIMATING SULFAMETHOXAZOLE IN PHARMACEUTICAL PREPARATIONS (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Four simple, sensitive, accurate, and rapid visible spectrophotometric methods (A, B, C and D) have been developed for the estimation of sulfamethoxazole in pharmaceutical Preparation. They are based on the diazotization of sulfamethoxazole with sodium nitrite and hydrochloric acid followed by coupling with N-(1-naphthyl ethylenediamine dihydrochloride (Method A) to form pink coloured chromogen, diphenylamine (Method B) to form pink coloured chromogen, β-napthol (in alkaline medium) (Method C) to form a orange yellow coloured chromogen and Resorcinol (in alkaline medium) (Method D) to form orange red coloured chromogen and exhibiting absorption maxima λmax at 536 nm, 516 nm, 477 nm and 502 nm respectively. The coloured chromogens formed are stable for more than 2 h. Beer's law was obeyed in the concentration range of 4 -12 µg mL-1 in method A , 2 – 10 µg mL-1 in method B, 5 – 25 µg mL-1 in method C and 1 – 5 µg mL-1 in method D respectively. The Results of the four analysis have been validated statistically and by recovery studies. The results obtained in the proposed methods are in good agreements with labeled amounts, when marketed pharmaceutical preparations are analyzed.